Monitoring and Control of Home Garage Access Using Iot-based Smartphones - Pratama, Bagas Yudhi; Sunardi, Sunardi (Signal and Image Processing Letters, 2020)
Technological developments are increasing to help facilitate human work, including developing control of equipment using smartphones. The system built in this study utilizes the Internet of Things (IoT) and the blynk application as a controller for the garage door opening and closing system using a smartphone to make it easier for owners to open and close the garage door without having to get out of the vehicle and do it manually. The system is built using the NodeMCU ESP8266 microcontroller which is connected to the blynk application to control the opening and closing of the garage door. Ultrasonic sensors are used to monitor the condition of the vehicles in the garage, while servo motors are used to open and close the garage door. This home garage access prototype using an IoT-based smartphone has succeeded in being able to open and close the garage door using the blynk application with a duration of 10 seconds when opening or closing the garage without having to do it manually. In this system, the user can monitor the condition of the garage for the presence or absence of vehicles by using the application.